Obtenção de pós e filmes finos do sistema SrTiO3:Nd - Silva, Marcia Rejane Santos da (2010)
SrTiO3 is a compound with perovskite structure usually found with cubic phase. This works reports the synthesis of powders and thin films of the undoped and Nd3+ doped SrTiO3, replacing Ti4+ or Sr2+ with the stoichiometries SrTi1-xNdxO3 (x = 0.00; 0.01; 0.02; 0.04) and Sr0.99Nd0.01TiO3. The powders were synthesized by the polymeric precursor method. The thin films were prepared by chemical solution deposition (CSD) using the spin coating technique and by pulsed laser deposition (PLD), being deposited on LaAlO3 (100), MgO (100), SrTiO3 (100), Al2O3-R, and SiO2. The structural and optical properties of these materials were evaluated by infrared spectroscopy, UV-vis spectroscopy, photoluminescent emission, micro Raman spectroscopy and X-ray diffraction (XRD) Rietveld refinement of the XRD patterns was realized for powder samples. Moreover the photocatalytic property was evaluated in the degradation of textile dyes. The coexistence of the cubic and tetragonal phases for SrTiO3 powders was confirmed after calcinations at 550 oC. For doped samples calcined at 700 oC, it was observed that the sites occupied by Nd3+ influenced in the amount of these phases, leading to a direct influence in the photoluminescent emission. Emission in the yellow region was observed, while temperature increase lead to a shift to the green region, with higher energy indicating that short range ordering occurred. Thin films deposited on LaAlO3 substrate showed high quality epitaxial growth by CSD and a very high quality by PLD. On MgO doping changed the film orientation. For deposition on Al2O3-R and SiO2, polycrystalline films were obtained. Photocatalytic degradation efficiency was similar in powders and undoped films, increasing for films doped with 4 % of Nd3+ when synthesis was done by PLD. Key words: